2013
DOI: 10.1007/s10120-013-0315-1
|View full text |Cite
|
Sign up to set email alerts
|

High-throughput mutation profiling identifies novel molecular dysregulation in high-grade intraepithelial neoplasia and early gastric cancers

Abstract: Background There is still no widely accepted molecular marker available to distinguish between gastric high-grade intraepithelial neoplasia (HG-IEN) and invasive early gastric cancer (EGC). Methods HG-IEN and EGC lesions coexisting in the same patient were manually microdissected from a series of 15 gastrectomies for EGC; 40 ng DNA was used for multiplex PCR amplification using the Ion AmpliSeq Cancer Panel, which explores the mutational status of hotspot regions in 50 cancer-associated genes. Results Of the 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
44
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 51 publications
(50 citation statements)
references
References 25 publications
(34 reference statements)
4
44
1
1
Order By: Relevance
“…As previously described for other tumor types [20,30,31], our results further support the clinical impact of targeted NGS on routinely processed samples. The integration of the mutational profiles with morphological and immunophenotypic data depicts a next-generation type of histopathological diagnosis.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…As previously described for other tumor types [20,30,31], our results further support the clinical impact of targeted NGS on routinely processed samples. The integration of the mutational profiles with morphological and immunophenotypic data depicts a next-generation type of histopathological diagnosis.…”
Section: Discussionsupporting
confidence: 74%
“…In the negative case (case 4), the immunohistochemical negativity may be explained by the fact that the R209 stop mutation likely prevents p53 stabilization, as reported for other similar mutations in TP53 [20]. An example of TP53 mutational results from paired samples is shown in figure 2.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, a number of recently published studies exploring gene mutations in gastric cancer using high-throughput methodologies (Nextgeneration sequencing and genotyping array) have confirmed CTNNB1 (the gene that encodes b-catenin protein) and APC as driver genes. Although with variations in prevalence, these studies revealed somatic mutations in both genes that might be relevant in gastric carcinogenesis [50][51][52][53][54][55] . In addition to multiple genetic alterations, the initiation and progression of gastric cancer are also associated to epigenetic changes [56,57] .…”
mentioning
confidence: 99%
“…HER2 immunoexpression was scored according to Rüsc-hoff et al [12]: 0, absence of immunoreactivity; 1?, tumor cell cluster with faint or barely perceptible membrane reactivity irrespective of percentage of immunoreactive cells; 2?, tumor cell cluster with weak to moderate (complete, lateral, or basolateral) reactivity irrespective of the percentage of immunoreactive cells; 3?, tumor cell cluster with strong (complete, lateral, or basolateral) reactivity irrespective of the percentage of immunoreactive cells; for scoring purposes any nuclear or cytoplasmic background staining was disregarded. The immunoexpression of CDX2 was considered positive when C25 % of the dysplastic cells displayed immunoreactivity [9]; immunoexpression of Ki-67 and TP53 was classified as absent/low when immunoreactivity was displayed in \50 % of the dysplastic cells and high in the presence of C50 % positive cells [13].…”
Section: Methodsmentioning
confidence: 99%